2016
DOI: 10.1007/s00216-016-0140-6
|View full text |Cite
|
Sign up to set email alerts
|

Development of a lateral flow immunoassay for rapid diagnosis of potato blackleg caused by Dickeya species

Abstract: Early detection of potato infections is essential for effective disease management. The aim of this study was to develop a lateral flow immunoassay (LFIA) for rapid detection of a serious potato disease, potato blackleg, caused by Dickeya dianthicola and Dickeya solani. Polyclonal antibodies specific to different strains of Dickeya were obtained from rabbits after immunization with bacterial cells of D. dianthicola and D. solani. Enzyme-linked immunosorbent assay testing with use of a wide range of bacterial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…The homogeneity of the GNPs in the solution and the absence of aggregates was shown by dynamic light scattering (DLS) (data shown in ESM, Figure 5 Sc), which also confirmed the dimensions of the nanoparticles (the average hydrodynamic diameter was 19.5 nm). Based on our previous experiences in the synthesis of GNP conjugates, we confirmed that spherical GNPs with diameters of 20–30 nm provided high stability to the conjugate [ 36 , 37 ]. Based on the characterized GNPs, we synthesized a GNP conjugate with the anti-PVY antibodies.…”
Section: Resultssupporting
confidence: 64%
“…The homogeneity of the GNPs in the solution and the absence of aggregates was shown by dynamic light scattering (DLS) (data shown in ESM, Figure 5 Sc), which also confirmed the dimensions of the nanoparticles (the average hydrodynamic diameter was 19.5 nm). Based on our previous experiences in the synthesis of GNP conjugates, we confirmed that spherical GNPs with diameters of 20–30 nm provided high stability to the conjugate [ 36 , 37 ]. Based on the characterized GNPs, we synthesized a GNP conjugate with the anti-PVY antibodies.…”
Section: Resultssupporting
confidence: 64%
“…Dickeya species can be identified using a series of biochemical tests paired with semi-selective media as well as lateral flow immunoassay [17]; neither method is time efficient or accurate. In contrast, molecular techniques are specific and sensitive for detection and differentiation of Dickeya to species [1821].…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 3 , the performance of our sensing platform is competitive with respect to other recent technologies in terms of sensitivity and the limit of detection. The two techniques based on lateral flow immune assays offer the great advantage to be very cheap and simple, two key aspects for on field analysis, but on the other hand they are not quantitative [ 24 , 25 ]. Papadakis and coworkers proposed an approach based on quartz crystal microbalance to detect DNA amplificons and they showed a LOD of 10 3 CFU/mL that is lower than our devices but their approach requires additional steps for DNA extraction from plant tissues and DNA amplification [ 26 ], which results in an increase in the cost and time necessary for the analysis.…”
Section: Discussionmentioning
confidence: 99%